Pengaruh Pupuk Kandang Ayam dan Trichoderma sp. Terhadap Pertumbuhan dan Hasil Tanaman Kacang Panjang di Tanah Gambut - Amira, Lola; Supriyanto, Supriyanto; Ramadhan, Tris Haris (Fakultas Pertanian Universitas Tanjungpura, 2024)
The development of long bean cultivation on peatlands has problems including poor macro and micro nutrients, acidic pH, and high cation exchange capacity (CEC). Efforts were made to overcome this problem by using chicken manure to improve the biological, physical and chemical properties of the soil, as well as adding Trichoderma sp to accelerate the decomposition of chicken manure as organic material. This research was carried out in Punggur Kecil Village, Sungai Kakap District, Kubu Raya Regency, which took place from March 1 2024 to May 13 2024. This research used a Factorial Completely Randomized Design (CRD) consisting of 2 treatment factors replicated as many times as 3 times, each replication consisted of 4 sample plants so there were 144 plants. The first factor in giving Chicken Manure (K) consists of 3 levels, namely k1 = 100 g/polybag, k2 = 200 g/polybag, k3 = 300 g/polybag and Trichoderma sp (T) consists of 4 levels, namely t1 = 0 g/ polybag, t2 = 5 g/polybag, t3 = 15 g/polybag, and t4 = 25 g/polybag. The observation variables observed in this research were plant height, root volume, plant dry weight, number of productive branches, number of plant fruit pods, fruit/plant weight, and pod/plant length. The results of this research show that giving chicken manure at a dose of 200 g/polybag is the best treatment for the growth and yield of long bean plants in peat soil. However, the dose of Trichoderma sp. best was not found in this study. There was an interaction between chicken manure and Trichoderma sp. to pod length per long bean plant